Dietary resilience of termite gut microbiota and enzymatic function reflects feeding strategy - Menezes, Letícia R.; Cairo, João Paulo L. F.; Costa-Leonardo, Ana Maria; Clerici, Maria Teresa Pedrosa Silva; da Costa Barreto, Isabela; dos Santos, Bianca Suriano Francisco; Arab, Alberto (Frontiers in Ecology and Evolution, 2025)
IntroductionTermites rely on complex gut microbiomes to digest lignocellulosic substrates, with dietary specialization potentially shaping microbial diversity and function. However, how gut microbiota respond to dietary shifts in generalist versus specialist termites remains poorly understood, especially among neotropical species.MethodsWe evaluated microbiota composition and enzymatic function in two higher termite species with contrasting feeding strategies: the polyphagous Silvestritermes euamignathus and the litter-feeding specialist Cornitermes cumulans. Workers from four colonies per species were subjected to artificial diets differing in fiber complexity. Gut samples were analyzed via 16S rRNA gene amplicon sequencing and enzymatic assays targeting lignocellulolytic activity. Bioinformatic and statistical analyses were performed to assess diversity, taxonomic shifts, and functional predictions.ResultsSilvestritermes euamignathus maintained stable microbial composition and enzymatic activity across diets, whereas C. cumulans exhibited shifts in bacterial abundance and a marked reduction in enzymatic function when exposed to complex artificial diets. Despite some taxon-specific responses in C. cumulans, overall microbial beta diversity remained stable in both species. Functional predictions revealed broader metabolic capacity and higher CAZyme expression in the generalist species under complex diets.DiscussionOur results suggest that microbial diversity and functional redundancy in S. euamignathus confer greater resilience to dietary perturbation, while C. cumulans displays limited plasticity consistent with dietary specialization. These findings have ecological implications, indicating that generalist termites may be better equipped to cope with environmental and resource shifts under changing climate scenarios.